Plate 12: Pyrotechnic staffs and wheels - Brawe, Hermann (Vollenkommene Unterweisung, wie Raketen, Feuer- Wasser- Sturm-Kugeln, Granaten, Pech-Sturm-Kräntze, und allerhand Lust und Ernsthaffte Feuer-wercke zubereiten, 1660)
Fig. 24: Fire-throwing pilgrim's staff. Fig. 25: Revolving pyrotechnic staff. Figs. 26-27: Fire wheels for use in water and their parts.
Keywords: Ordnance; Explosives; Artillery; Fireworks